Pairing Principles From Participatory Design Research and Design-Based Research to Center Latina/x Youth in an Afterschool Program - Catherine L. Dornfeld Tissenbaum; Idalia Nunez; Mónica González Ybarra; Citlalli Garcia (International Journal of Qualitative Methods)
Participatory Design Research (PDR) aims to dismantle researcher-participant hierarchies through inclusion and elevation of participants’ voices in the design, implementation, and analysis of educational interventions. PDR builds upon Design-Based Research (DBR) which investigates the effectiveness of educational interventions in authentic settings through iterative design and ongoing analysis. This paper describes how we drew from both PDR and DBR to center participants in the iterative design of an afterschool program about Latina/x youth in museums. We used multiple qualitative methods to analyze how a cohort of eight Latina/x middle-school girls responded to the initial design of activities, which led to mid- and post-implementation changes to the design of the afterschool program as afforded by PDR and DBR. By viewing the girls’ rejection and redirection of planned activities as productive, we gained opportunities to learn what topics were salient to the girls, such as events from the school day. In turn, our participants increasingly “drove” the programming and co-created museum exhibits that represented their identities, communities, linguistic diversity, and artistry. From these findings, we discuss how drawing from PDR and DBR allowed us to center participants in the design of the afterschool program and museum exhibition while allowing justified pivots in our research plan. Notably, we situate our project’s methodology between PDR and DBR to illustrate how these methodologies create space for participant-driven design even when participant-led analysis is constrained by logistics and resources. We also note the emotional and mental labor invested in engaging in participant-centered research. Last, we contribute design recommendations for researchers and designers who aim to serve marginalized youth, amplify their voices, and counter epistemic injustice.